2014
DOI: 10.4067/s1726-569x2014000100013
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of Pakistani pharmacy and medical students’ knowledge of black box warnings

Abstract: Food and Drug Administration delivers the black box warnings (BBW) which should appear on the leaflets of medicines for patient awareness and the prescription of drugs indicating its highly fatal adverse effects to human body. The aim of this study was to assess the knowledge of Pakistani pharmacy and medical students about BBW. A questionnaire containing contents about BBW was given to the 1 st , 2 nd and 3 rd professional year pharmacy and medical students from different pharmacy and medical institutes. A 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…These studies have shown insufficient knowledge of physicians and pharmacists toward the BW (19,31). Other studies investigating the knowledge of BW among pharmacy and medical students reported a low level of knowledge which was directly proportionate to their study years (32,33). Since lack of information regarding BW may put patients at increased risks, the FDA along with other health authorities should adopt an appropriate mechanism of communication for such warnings and should also develop systematic feedback to ensure that all BW are communicated to HCPs across the world.…”
Section: Discussionmentioning
confidence: 98%
“…These studies have shown insufficient knowledge of physicians and pharmacists toward the BW (19,31). Other studies investigating the knowledge of BW among pharmacy and medical students reported a low level of knowledge which was directly proportionate to their study years (32,33). Since lack of information regarding BW may put patients at increased risks, the FDA along with other health authorities should adopt an appropriate mechanism of communication for such warnings and should also develop systematic feedback to ensure that all BW are communicated to HCPs across the world.…”
Section: Discussionmentioning
confidence: 98%